Quality assessment of pharmaceutical care to patients with headaches using the simulated patient method: interaction practice - O. V. Reshetko; A. I. Grishin (Izdatelstvo OKI, 2023)
Relevance. WHO assesses headaches as a global world problem. Russia occupies a leading position in the prevalence of primary headaches. Headaches are one of the most common reasons for visiting a pharmacy for self-medication. The interaction of the pharmacist and the visitor with the headache problem in general determines the quality of pharmaceutical care.Aim. To assess the practice of the interaction between a patient with a headache and a pharmacist using the simulated patient method.Materials and methods. Trained simulated patients (women aged 20, 40 and 58 years) visited a total of 101 pharmacies. The dialogue was recorded on a voice recorder, all the features of the interaction were additionally recorded aﬅer the visit. Special forms were ﬁlled out based on the information received. The data was processed using Microsoﬅ Excel 2010 and STATISTIKA 10.0.Results. The average interaction time was 98.2±3.8 seconds. There was a high frequency of spontaneous recommendations without preliminary questions (66.3%), a small number of questions asked (0.84±0.1). These indicators practically did not depend on various factors (type of pharmacy organization, age of the pharmacist, age of the simulated patient, the presence of a queue, and others).Conclusion. The results of the study demonstrate a low level of interaction between pharmacists and visitors with a headache, as well as a practical absence of involvement in the process of providing pharmaceutical care, which negatively aﬀects its quality: frequent spontaneous recommendations, short consultations and rare questions. The approach to the interaction of pharmacists with visitors with headaches is formal and requires standardization.